The Influence of Interactive Learning Media and Learning Motivation on Student Learning Outcomes in Science Subjects at Elementary School Cluster 1, Poigar District - Glendra Robot; Aldjon N. Dapa; Zoja F. Sumampow (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to analyze the effect of interactive learning media and learning motivation on students’ learning outcomes in the subject of Natural and Social Sciences at Elementary School Cluster 1, Poigar District. Interactive learning media is believed to enhance students’ engagement through the integration of text, images, audio, video, and animation, thereby creating a more attractive and meaningful learning experience. In addition, learning motivation plays an important role as a psychological drive that influences students’ persistence and achievement in the learning process. This research employed a quantitative approach with a 2×2 factorial quasi-experimental design involving an experimental class and a control class. The subjects of the study were 40 fourth-grade students. The research instruments included an IPAS learning achievement test, a learning motivation questionnaire, and an observation sheet on the use of interactive learning media, all of which had been tested for validity and reliability. Data analysis was conducted using the independent samples t-test and two-way ANOVA to examine the main effects and interaction between variables. The results showed that interactive learning media and learning motivation significantly affected students’ learning outcomes, both partially and through interaction effects. The average posttest score of the experimental class (87.3) was higher than that of the control class (74.7), with N-gain scores of 73.05% (high category) and 43.51% (moderate category), respectively. In conclusion, interactive learning media and learning motivation significantly influence students’ learning outcomes in IPAS. The use of interactive media supported by high learning motivation can optimally improve students’ academic achievement.